Measurement of tungsten reactivity worth on VENUS-II light water reactor and validation of evaluated nuclear data. (September 2018) - Jiang, Wei; Gu, Long; Zhou, Qi; Zhu, Qing-Fu; Chen, Liang; Liu, Xing-Quan; Zhang, Lu; Li, Jin-Yang; Fan, Da-Jun; Zhang, Suyalatu; Xu, Hu-Shan; Chen, Hong-Li; et al.
Abstract: In this article, we report a benchmark experiment of the tungsten reactivity worth under a super-critical state which has been conducted at the VENUS-II facility of CIAE in Beijing. The cylindrical tungsten target reactivity worth was measured and extracted as −1.234 ± 0.114 × 10 −3 Δk/k using a period method. The resultant tungsten reactivity worth was compared with those from the MCNP Monte Carlo simulations with five evaluated libraries, i.e., ENDF/B-VII.0, ENDF/B-VII.1, CENDL-3.1, JENDL-4.0 and JEFF-3.2. It is found that the results from the MCNP simulations with ENDF/B-VII.0, ENDF/B-VII.1, JENDL-4.0 and JEFF-3.2 are overestimated, whereas that of CENDL-3.1 is underestimated, and those from the MCNP simulations with the ENDF/B-VII.1 and ENDF/B-VII.0 libraries show slight better agreement with the experiment data within errors. A correlation analysis was used to address these issues. We conclude that it is the discrepancy of the (n, γ) channel at the epithermal neutron region that mainly results in the difference between the measured and MCNP simulated tungsten reactivity worth values.